Redox Metabolism in Ecophysiology and Evolution, 2nd Edition - Marko D. Prokić; Marcelo Hermes-Lima; Daniel C. Moreira (Antioxidants)
The ability of organisms to regulate the production of reactive oxygen and nitrogen species (RONS), manage pro-oxidant activity, and make use of redox pathways has significantly influenced their evolution [...]